Competition between a Lawn-Forming Cynodon dactylon and a Tufted Grass Species Hyparrhenia hirta on a South-African Dystrophic Savanna - Zwerts, J. A.; Prins, H. H. T.; Bomhoff, D.; Verhagen, I.; Swart, J. M.; de Boer, W. F. (PloS one, 2015)
South African savanna grasslands are often characterised by indigestible tufted grass species whereas lawn grasses are far more desirable in terms of herbivore sustenance. We aimed to investigate the role of nutrients and/or the disturbance (grazing, trampling) by herbivores on the formation of grazing lawns. We conducted a series of common garden experiments to test the effect of nutrients on interspecific competition between a typical lawn-forming grass species (Cynodon dactylon) and a species that is frequently found outside grazing lawns (Hyparrhenia hirta), and tested for the effect of herbivore disturbance in the form of trampling and clipping. We also performed a vegetation and herbivore survey to apply experimentally derived insights to field observations. Our results showed that interspecific competition was not affected by soil nutrient concentrations. C. dactylon did show much more resilience to disturbance than H. hirta, presumably due to the regenerative capacity of its rhizomes. Results from the field survey were in line with these findings, describing a correlation between herbivore pressure and C. dactylon abundance. We conclude that herbivore disturbance, and not soil nutrients, provide C. dactylon with a competitive advantage over H. hirta, due to vegetative regeneration from its rhizomes. This provides evidence for the importance of concentrated, high herbivore densities for the creation and maintenance of grazing lawns.